Pengaruh Penggunaan Mobile Health dan Fitur Pemantauan Terhadap Gaya Hidup Sehat: Literatur Review - Hasanah, Uswatul; Zahira, Sayyidati; Barokah, Wuni; Hajijah, Sri (PT. Alahyan Publisher Sukabumi, 2025)
The m-health application provides various information needed by the general public, not only information but easy access. One example is the use of health applications, with technology, namely mobile health applications, it can make things easier for people, especially in the health sector. Especially in the health sector, it makes it easy for users to monitor health remotely and various other features to improve the quality of health services for the community. This research examines the effect of using mobile health and monitoring features on a healthy lifestyle. This type of research uses literature review techniques. This research was conducted using the Google Scholar database by searching for several previous articles related to the use of mobile health applications in improving the quality of health services. With the development of mobile health technology in the world of health, it turns out that it has a good influence on society. Mobile health is an innovation in the health sector that uses media to access digital-based health information and services.